2022
DOI: 10.1093/molbev/msac180
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary Tuning of Transient Receptor Potential Ankyrin 1 Underlies the Variation in Heat Avoidance Behaviors among Frog Species Inhabiting Diverse Thermal Niches

Abstract: Environmental temperature is a critical factor for all forms of life, and thermal tolerance defines the habitats utilized by a species. Moreover, the evolutionary tuning of thermal perception can also play a key role in habitat selection. Yet, the relative importance of thermal tolerance and perception in environmental adaptation remains poorly understood. Thermal conditions experienced by anuran tadpoles differ among species due to the variation in breeding seasons and water environments selected by parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Among thermosensitive TRP channels, TRPA1 and TRPV1 have been an active area of research at elucidating the physiology and evolution of thermal sensitivity in non-model and wild organisms (Oda et al, 2019;Ohkita et al, 2012;Saito et al, 2012Saito et al, , 2016Saito et al, , 2019Saito et al, , 2022. Both TRPA1 and TRPV1 have been reported as heat-sensitive channels in most species studied investigated, with the exception of TRPA1 in mammals and Caenorhabditis elegans (Chatzigeorgiou et al, 2010;Saito et al, 2014).…”
Section: Mechanisms Of Temperature Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among thermosensitive TRP channels, TRPA1 and TRPV1 have been an active area of research at elucidating the physiology and evolution of thermal sensitivity in non-model and wild organisms (Oda et al, 2019;Ohkita et al, 2012;Saito et al, 2012Saito et al, , 2016Saito et al, , 2019Saito et al, , 2022. Both TRPA1 and TRPV1 have been reported as heat-sensitive channels in most species studied investigated, with the exception of TRPA1 in mammals and Caenorhabditis elegans (Chatzigeorgiou et al, 2010;Saito et al, 2014).…”
Section: Mechanisms Of Temperature Sensingmentioning
confidence: 99%
“…In amphibians, where sex determination occurs during or after the larval stage, thermal perception through TRP channels may indirectly influence their own sex by inducing thermoregulatory behaviors. Behavioral assays have shown that a TRPA1 agonist sensitizes heat avoidance behavior in the Japanese stream tree frog ( Buergeria japonica ) and Buerger's frog ( B. buergeri ), implying that TRPA1 also functions as a nociceptive heat sensor in these amphibians (Saito et al, 2022). The relationship between thermal effects on sex determination and thermoregulatory behaviors remains essential and warrants further investigation to comprehend the significance of temperature perception in amphibian sex determination.…”
Section: Mechanisms Of Temperature Sensingmentioning
confidence: 99%